Web-Based Animation Video for Student Environmental Education at Elementary Schools - Safitri, Desy; Lestari, Ika; Maksum, Arifin; Ibrahim, Nurzengky; Marini, Arita; Zahari, Musril; Iskandar, Rossi (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This research and development aim at knowing the effectiveness of web-based animation videos application on environmental education of elementary school students in East Jakarta in Indonesia. Web-based animation videos for environmental education produced consisted of climate change, mangrove forest, waste recycling, biodiversity, and ozone depletion animation video pages. Student environmental education measured was related to satisfying student natural curiosity, enhancing environmental awareness, and strengthening student pro-conservation values. In the conclusion, it is highlighted that there is a positive effect of web-based animation videos application on student environmental education at elementary school students in Jakarta in Indonesia